2009
DOI: 10.1093/geronb/gbp028
|View full text |Cite
|
Sign up to set email alerts
|

Religion and the Quality of Life in the Last Year of Life

Abstract: Overall, QOL in the last year of life is positively related to religious involvement, particularly its more subjective dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 22 publications
4
47
1
8
Order By: Relevance
“…Estudo transversal, com 499 idosos avaliando a associação de religião com a qualidade de vida no último ano de vida, observou resultado semelhante ao do presente trabalho 17 , assim como pesquisa realizada com idosos da América Latina e do Caribe, segundo a qual filiação religiosa estava associada com pior avaliação de saúde, embora essa associação não se mantivesse após ajuste por capacidade funcional 16 . O achado é interessante por contrariar a crença comumente difundida de associação positiva entre religião e saúde.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estudo transversal, com 499 idosos avaliando a associação de religião com a qualidade de vida no último ano de vida, observou resultado semelhante ao do presente trabalho 17 , assim como pesquisa realizada com idosos da América Latina e do Caribe, segundo a qual filiação religiosa estava associada com pior avaliação de saúde, embora essa associação não se mantivesse após ajuste por capacidade funcional 16 . O achado é interessante por contrariar a crença comumente difundida de associação positiva entre religião e saúde.…”
Section: Discussionunclassified
“…Ramos 12 observou que os indivíduos de segmentos sociais mais desfavorecidos, principalmente com menor escolaridade, apresentaram pior autoavaliação de saúde. A influência da filiação religiosa na autoavaliação de saúde tem sido analisada por alguns autores, mas os achados não tem sido consistentes 15,16,17 .…”
Section: Introductionunclassified
“…ADLs include such activities as walking, cooking, bathing, performing household chores, and other activities requiring physical movement (Rajan, Hebert, Scherr, Mendes de Leon, & Evans, 2013). Idler, McLaughlin, and Kasl (2009) measured correlations between religious activities and ADLs and found that religiosity serves as a defense mechanism against depression in patients with severe functional disabilities. They found that prayer helps patients cope with worsening health conditions, while religious participation brings about social support, family togetherness, and personal acceptance of their condition.…”
Section: Health Outcomesmentioning
confidence: 99%
“…As chronic conditions increase, elders turn to religion with the challenge of trying to regain normal lives (Idler et al, 2009). Studies show religious coping used among the depressed elderly appears to result in positive outcomes.…”
Section: Downloaded By [University Of Chicago Library] At 00:50 20 Nomentioning
confidence: 99%
See 1 more Smart Citation